A Survey of Attitudes and Practices Regarding the Use of Steroid Supplementation in Pediatric Sepsis. Issue 10 (October 2015) - Carmean, Amanda; Fortenberry, James D.; McCracken, Courtney; Hebbar, Kiran B.
<x xml:space="preserve">Abstract</x> Objective Although corticosteroid (CS) supplementation for pediatric septic shock (PSS) is recommended by American College of Critical Care Medicine sepsis guidelines, most data are based on adult trials. Standardized protocols for stimulation testing for adrenal insufficiency (AI) and CS treatment in children have been reported, but the current state of CS use and protocols have not been evaluated in pediatric intensive care units in the United States. We surveyed a group of pediatric intensivists to assess current approaches. Design An electronic survey with 54 questions on attitudes and current use of CSs was distributed to 49 pediatric critical care and 49 pediatric endocrinology fellowship program directors. Main Results Twenty-one (43%) of 49 critical care recipients completed the survey. Eleven (52%) were from medical/surgical units and 10 (48%) were from medical/surgical/cardiac units, with a median of 24 beds and 1614 annual admissions. Thirteen (62%) of 21 recipients rated the importance of steroids in the management of PSS as greater than 4 or 5, with 1 being of no importance and 5 of critical importance. Nineteen (90%) of 21 recipients thought AI occurs "sometimes" or "often" in septic shock. Adrenocorticotropin stimulation testing was frequently used (19 of 21; 90%) but not in protocol. Eighteen (85%) of 21 recipients agreed that "some should" receive "steroids as it improves outcome" and 9% agreed that "most should…" Fourteen (66%) of 21 recipients reported that more than 50% of patients with vasopressor-refractory PSS receive CSs. Hydrocortisone was used in 21 (100%) of 21 recipients, but dosing and duration were variable. Concerns to limit/avoid CSs included hyperglycemia (38%), superinfections (81%), and critical illness myopathy (57%). Only 3 (14%) of 21 recipients reported that they used a CS protocol for PSS. Sixteen (76%) of 21 recipients were not comfortable drawing conclusions from adult studies for PSS. Nineteen (90%) of 21 recipients agreed that it would be important to perform a randomized trial for CS use in PSS. Conclusions Corticosteroids are used at most centers for treatment of PSS, but significant variation in attitudes and use exists. Most centers identify AI as frequent; most report variable use of stimulation testing and dosing of CSs. Few centers currently use a standard protocol for diagnosis and treatment. Interest in performing a randomized trial for CSs remains because in part of reluctance to accept adult trial data.